Segmented metal foam flow fields with in-plane porosity variation for enhanced reactant distribution and hydrogen utilization in PEM fuel cells - Keikhaei, M. J.; Kermani, M. J.; Genceli, H.; Maleki, M. E.; Moein-Jahromi, M.; Heidary, H. (PERGAMON-ELSEVIER SCIENCE LTD, 2026)
This study addresses the challenge of uneven reactant distribution in PEM fuel cells (PEMFCs) when employing homogeneous metal foams as flow distributors by introducing, for the first time, a segmented foam architecture. Unlike conventional homogeneous foam designs, a novel in-plane porosity variation concept, referred to here as Variable Porosity Foam (VPF), is investigated, consisting of 25 discrete 1 x 1 cm2 segments within a 5 x 5 cm2 active area. This segmentation is intended to maintain fabrication simplicity while enabling spatial control of transport properties. Three-dimensional, two-phase CFD simulations are performed to compare the VPF configuration against a baseline homogeneous metal foam. The results demonstrate that the VPF design enhances oxygen availability and improves current density uniformity at the catalyst layer interface. For instance, at 0.4 V, the VPF configuration yields a 23.9% increase in average oxygen mole fraction and a 29.4% improvement in current density compared to the baseline case. These findings highlight the potential of segmented metal foams for improving reactant distribution and utilization, contributing to more efficient hydrogen use and enhanced performance in PEMFC systems.
Keywords: PEM fuel cell flow field; Segmented variable-porosity foam; Metal foam-based flow field (MFF); CFD modelling; Reactant uniformity; Cathode flow distributor; CLIMATE-CHANGE; PERFORMANCE; SIMULATION; TRANSPORT; GRAPHENE; DESIGN; Chemistry; Electrochemistry; Energy & Fuels